Natural Language Processing in Economics and Finance : literature review and applications to Monetary Policy Communication - Lucchetti, Alexandre Henrique (2025)
Tese (doutorado)—Universidade de Brasília, Faculdade de Administração, Contabilidade, Economia e Gestão de Políticas Públicas, Departamento de Economia, Brasília, 2025.